2016
DOI: 10.19046/abp.v03i03.04
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Adipose derived Mesenchymal Stem cells (ADMSCs) in Madras Red Sheep (Ovis aries).

Abstract: ADMSCs were cultured upto passage 2 (P 2 ). Characterization was done by using transcription factors namely Oct4 and Sox2 at P 0 level and was demonstrated by immunofluroscence technique. Immunophenotyping of ovine ADMSCs was done by using CD34 and CD44 monoclonal antibodies at P 0 and P 1 levels by using flow cytometry. At P0 level, 30.14 per cent ADMSCs were positive to CD44 and 13.83 per cent were positive for CD34 antibodies. At P 1 level, 40 per cent and 7.13 per cent cells were positive for CD44 and CD34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On day five post incubation the cells attained about 60-70 per cent confluency at P1. According Beaulah et al, (2016) in Madras Red Sheep, subcutaneous and omental AD-MSCs took six days to reach same percentage in P1. The initial culture contained heterogeneous cell population with round and fibroblastic cell, upon culture, the number of rounded cell decreased and fibroblastic cells started increasing.…”
Section: Subculture Of Fad-mscsmentioning
confidence: 95%
See 2 more Smart Citations
“…On day five post incubation the cells attained about 60-70 per cent confluency at P1. According Beaulah et al, (2016) in Madras Red Sheep, subcutaneous and omental AD-MSCs took six days to reach same percentage in P1. The initial culture contained heterogeneous cell population with round and fibroblastic cell, upon culture, the number of rounded cell decreased and fibroblastic cells started increasing.…”
Section: Subculture Of Fad-mscsmentioning
confidence: 95%
“…According to Beaulah et al, (2016) and Fadel et al, (2011), the plastic adherence of AD-MSC was observed after 24 hours in primary culture. Similarly in buffalo, adherence was noticed after 24 hours (Hepsibha et al, 2011).…”
Section: Seeding Of Fad-mscsmentioning
confidence: 96%
See 1 more Smart Citation
“…Hoechst or propidium iodide was added and kept at room temperature for 1 min for counterstaining. After washing three times, the plate was examined under a fluorescence microscope (Beaulah et al 2016). Negative controls without primary antibody were used to determine if the secondary antibody is binding nonspecifically to cellular components, resulting in false positives or nonspecific binding.…”
Section: Characterisation Of Sscsmentioning
confidence: 99%